Geological and geomorphological characteristics of the Paleolithic sites of the northern foothills of the Ile Alatau ridge (Journal of Geography and Environmental Management, 2019)
In recent years, specialists of the laboratory of "geoarcheology" of the faculty of history, archeology and ethnography of the Kazakh National University named after al-Farabi, together with the staff of the geographical faculty within the northern foothills of the Ile Alatau ridge, conducted geoarchaeological research. The study revealed several Paleolithic sites, the study of which is of great importance for solving the problem of the settlement of the territory of south-eastern Kazakhstan by primitive people of the Stone Age. Materials from the sites Kastek, Kyzylauz-2, Temirlik and Sharyn give an idea of the ways and times of settlement of one of the interesting regions of Kazakhstan - Zhetysu. The variety of geomorphological positions and the finding of artifacts in different layers of quaternary sediments, allows the use of geological and geomorphological methods to highlight the age of sites of ancient human.. Paleolithic sites were found on the valleys of small rivers when they left the mountains in the foothill plans, on the removal cones of temporary watercourses. Stone tools found in the Kyzylaus and Maybulak sites were mainly made of porphyrite. Their sources are the effusive errays of the Lower Carboniferous, widely delevoped in the western spurs of the watershed of the Ile Alatau ridge. The products of destruction of effusive rocks, which formed as a result of their weathering, were activety washed away by mountain rivers into the foothill zones, where they were deposited in the mouth of small rivers and on cones removal of temporary streams.